Development and Acceptability of Tuyong Tawilis (Sardinella tawilis) Flavored Noodle - Lazaro, John Marco A.; Maroma, Dolly P.; Maroma, Allen N. (Future Science / FSH-PH Publications, 2025)
This study examines the role of food innovation in the global noodle market, particularly addressing the nutritional limitations of many instant noodle products. It emphasizes the need for healthier alternatives to meet the growing demand from health-conscious consumers. Specifically, the study advocates for the development of high-protein noodle variants enriched with local flavors, such as